2018
DOI: 10.1097/anc.0000000000000451
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Stress Behaviors, Autonomic Indices, and Maternal Perceptions of Infant Colic

Abstract: Further study in a larger sample is needed to determine whether behavioral stress measures and HF-HRV may be useful to determine colic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 67 publications
1
21
0
Order By: Relevance
“…Postprandial HRV data were obtained in two consecutive afternoons between noon and 5 pm for 30 to 40 minutes between days 5 and 8 of life and weekly thereafter until 35 weeks PMA using a portable data acquisition system with BioBench (National Instruments, Austin, TX) software and later analyzed by spectral analysis offline using MindWare HRV version 2.51 (Mind-Ware Technologies, LTD, Gahanna, OH). 24 Neonatal morbidity outcomes (i.e., total days on ventilation, total days on oxygen, and length of hospital stay) and short-term developmental outcomes (i.e., PMA at full oral feedings and PMA at discharge) were recorded from infants' EMR weekly from birth through discharge. SSC information was documented by nursing and inventoried retrospectively by research staff from birth through day 21 of life from infants' EMR.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Postprandial HRV data were obtained in two consecutive afternoons between noon and 5 pm for 30 to 40 minutes between days 5 and 8 of life and weekly thereafter until 35 weeks PMA using a portable data acquisition system with BioBench (National Instruments, Austin, TX) software and later analyzed by spectral analysis offline using MindWare HRV version 2.51 (Mind-Ware Technologies, LTD, Gahanna, OH). 24 Neonatal morbidity outcomes (i.e., total days on ventilation, total days on oxygen, and length of hospital stay) and short-term developmental outcomes (i.e., PMA at full oral feedings and PMA at discharge) were recorded from infants' EMR weekly from birth through discharge. SSC information was documented by nursing and inventoried retrospectively by research staff from birth through day 21 of life from infants' EMR.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, the following frequency range was utilized while analyzing preterm neonates' cardiac vagal tone: high-frequency (HF)/respiratory sinus arrhythmia band ¼ 0.3 to 1.3 Hz, to correlate with the faster resting breathing rates of 20 to 80 breaths/min in the preterm neonates in our sample population. 24,27 Using fast Fourier transform, spectral analysis was conducted on a mean of 13 120-second segments of R-R wave data collected from two consecutive afternoons during 30 to 40 minutes HRV measurement sessions. Each segmental analysis was manually screened to be free from movement artifact and ectopic beats.…”
Section: Methodsmentioning
confidence: 99%
“…Increased HRV, and specifically HF-HRV power, indicate preterm infants' ANS stability and ability to modulate stress, where decreased HRV can be correlated with pathological conditions [51]. According to the neurovisceral integration model, HRV analysis provides a unique insight to brain activity and the heart-brain connection, as it indexes the cardiac vagal tone, and may reflect the functionality of neural networks that are implicated in regulation of physiological, affective, and cognitive processes [52].…”
Section: Discussionmentioning
confidence: 99%
“…Real-time HRV helped identify stress-related behaviors, which are difficult to visually recognize: for example, LF increased during stress behaviors, whereas HF increased with self-consoling behaviors (Gardner et al, 2018). Moreover, real-time HRV monitoring-as revealed by changes in short-and long-term metrics, such as RMSSD, LF/HF, SampEn, and DFA α1 (but also SDNN, LF, HF, SD1, SD2, ApEn, and DFA α2) or in the newborn infant parasympathetic evaluation (NIPE)-correlated with nociceptive events, such as heel stick (Weissman et al, 2012;Butruille et al, 2015).…”
Section: The Clinical Usefulness Of Real-time Hrv To Monitor Newbornsmentioning
confidence: 99%
“…Several studies showed that HRV correlates with the newborn's stress and stress-related behaviors (Gardner et al, 2018;Hashiguchi et al, 2020), and that it could predict the baby's overall wellbeing and future neurological development. HRV could also accurately identify short-and long-term complications, such as the risk of sepsis (Javorka et al, 2017;Oliveira et al, 2019b;Kumar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%